Born to be beautiful: Season of birth influences adult females’ physical attractiveness - KANONOWICZ, MICHAŁ; SOROKOWSKI, PIOTR; SOROKOWSKA, AGNIESZKA (Journal of Education Culture and Society, 2020)
Birth month in humans is associated with certain biological variables such as reproduc-tive success, health and mortality rate. At the same time, physical attractiveness is regarded as one of the reliable markers of human health and genetic quality, which suggests that female attractiveness may vary according to their season of birth. To test this hypothe-sis, ratings of females’ photographs from a popular Polish social networking website were analyzed. The sample included 5294 females aged 21-23 years. Results demonstrated that females born in spring (May) were rated as being significantly more attractive than those born in autumn (September and November).